Low-stacking-pressure sulfide all-solid-state battery composite cathode material and preparation method and application thereof

CN122992033APending Publication Date: 2026-10-27CENT SOUTH UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611243104.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0010]综上所述,现有技术虽能通过颗粒级配优化、表面包覆或梯度结构设计在一定程度上改善复合正极的离子传输性能,但仍存在以下共性不足:其一,所形成的界面大多仍属于物理接触界面,在低堆叠压力条件下容易发生接触退化,导致界面阻抗持续增加;其二,表面包覆类技术难以同步构建颗粒界面与体相内部的连续长程离子传输网络;其三,现有技术普遍缺乏针对正极颗粒尺度界面结构稳定化的系统设计,难以同时兼顾界面离子传输能力、长程离子输运能力以及循环过程中的界面力学稳定性

Benefits of technology

(1)本发明采用低能机械+化学热处理工艺,将纳米级硫化物固态电解质、高镍层状氧化物正极活性材料以及界面活化剂进行预构筑处理,使纳米级硫化物固态电解质优先吸附并附着于正极活性材料颗粒表面,同时实现界面活化剂在正极/固态电解质接触区域的均匀分布,形成具有反应活性的纳米级界面预构筑层。与传统将正极活性材料、固态电解质及导电剂直接机械混合的方式相比,本发明能够使固态电解质组分由随机分布转变为正极颗粒表面优先富集,提高正极活性材料与固态电解质之间的有效接触面积,减少界面空隙及局部离子传输断裂区域,缩短锂离子由固态电解质向正极颗粒内部迁移的路径,从而降低界面离子迁移阻抗并提高正极活性材料利用率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992033A_ABST
    Figure CN122992033A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of sulfide all-solid-state battery composite positive electrode material, and specifically discloses a low stacking pressure sulfide all-solid-state battery composite positive electrode material and a preparation method and application thereof. The composite positive electrode material comprises a high-nickel layered oxide positive electrode material, a nanoscale and microscale sulfide solid electrolyte, an interface activator and an amorphous self-adaptive ion buffer material; the nanoscale sulfide solid electrolyte is attached to the surface of the positive electrode particles to form an interface pre-constructed layer, the interface activator is heat-treated to induce the interface reconstruction of the positive electrode and the nanoscale electrolyte to form an interface transition layer, the microscale sulfide solid electrolyte forms a continuous long-range ion transmission skeleton, the amorphous self-adaptive ion buffer material fills the inter-particle gaps to form an amorphous ion buffer layer, each layer is gradiently distributed along the surface-to-interstitial direction of the particles, and a multi-scale cooperative ion transmission network is formed. The preparation method is also disclosed. The material has low interface impedance and excellent cycle stability under low stacking pressure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sulfide all-solid-state battery composite cathode materials, and particularly to a low-stacking-pressure sulfide all-solid-state battery composite cathode material, its preparation method, and its application. Background Technology

[0002] With the urgent demand for high-energy-density energy storage systems in fields such as new energy vehicles, large-scale energy storage, and aerospace, the energy density and safety of lithium-ion batteries have become key factors restricting their further development. Sulfide-based all-solid-state lithium-ion batteries, which replace traditional organic liquid electrolytes with non-flammable sulfide solid electrolytes, offer advantages such as high safety, high energy density, and a wide operating temperature range, and are considered an important development direction for next-generation high-performance energy storage systems. Among these, high-nickel layered oxide cathode materials (such as LiNi) are... 0.9 Co 0.05 Mn 0.05 O2 has shown broad application prospects in sulfide all-solid-state batteries due to its high specific capacity and energy density.

[0003] However, unlike liquid batteries where the electrolyte can fully wet the electrode particle surface, lithium-ion transport in sulfide all-solid-state batteries relies on a continuous and stable solid-solid interface between the positive electrode active material and the solid electrolyte. During battery operation, the contact area between the solid particles within the composite positive electrode directly determines the continuity of the ion transport channel and the magnitude of the interfacial impedance. Especially under conditions of reduced stacking pressure (0.1~50MPa)—which is both a necessary requirement for large-scale manufacturing processes and an important direction for reducing the structural complexity of battery systems—the contact area between the solid particles within the composite positive electrode decreases significantly, easily leading to interfacial contact failure, interruption of ion transport channels, and a continuous increase in interfacial impedance, thus severely restricting the battery's capacity utilization and cycle stability. Therefore, how to construct a stable and efficient positive electrode / solid electrolyte interface structure under low stacking pressure conditions has become a major technical bottleneck restricting the industrialization of sulfide all-solid-state batteries.

[0004] Extensive research has been conducted on the aforementioned solid-solid interface problem, primarily focusing on improving the ion transport performance of composite cathodes through methods such as particle size distribution optimization, surface coating modification, and structural gradient design. However, the following shortcomings still exist: Patent CN121964524A discloses a composite cathode material and its preparation method, which improves the overall ion transport capability of the composite cathode by controlling the proportion and distribution of solid electrolyte particles of different sizes. However, this technical solution is essentially still a random mixture of solid electrolyte particles of different sizes, and the nanoscale solid electrolyte particles are not preferentially distributed on the surface of the cathode active material. Under reduced stacking pressure, there is still a problem of insufficient local contact on the cathode particle surface; at the same time, the ion transport pathways formed between particles mainly rely on mechanical contact between particles, resulting in limited interfacial structural stability and difficulty in further reducing interfacial impedance.

[0005] Patent CN121922591A discloses a composite cathode material and its preparation method, which improves the interfacial contact between the cathode active material and the solid electrolyte by introducing a solid electrolyte into the composite cathode. Although this technical solution can improve the initial electrochemical performance of the composite cathode, its interface is mainly formed through physical mixing, and the interfacial bonding strength is limited. During cycling, especially under low stacking pressure conditions, the contact state between the cathode active material and the solid electrolyte is prone to degradation, leading to a continuous increase in interfacial impedance and thus affecting cycle stability.

[0006] Patent CN111509293A discloses a cathode material with a surface-coated solid electrolyte layer and its preparation method, which increases the interfacial contact area by constructing a solid electrolyte coating layer on the surface of the cathode material particles. However, since the solid electrolyte is mainly concentrated on the surface of the cathode particles, it mainly improves the local interfacial ion transport process, making it difficult to simultaneously construct a continuous long-range ion transport network that runs through the entire composite cathode. When the composite cathode loading increases or the stacking pressure decreases, interparticle ion transport remains a limiting factor.

[0007] Patent CN116706064A discloses an interface-modified sulfide all-solid-state battery cathode material and its preparation method, which improves the contact state between the cathode and the solid electrolyte through interface modification. However, this technical solution mainly focuses on the initial improvement of the interface contact, and pays insufficient attention to how to maintain its stability during long-term cycling after the interface is formed. Especially under low stacking pressure conditions, the interface contact state may still gradually deteriorate with cycling.

[0008] Patent CN117059879B discloses a composite cathode material and an all-solid-state battery, which improves electrochemical reaction kinetics by constructing an interface modification layer. However, this technical solution mainly focuses on local optimization of the interface region and fails to simultaneously consider the synergistic matching relationship between particle surface interface contact and long-range ion transport inside the composite cathode, thus limiting the improvement of ion transport capability.

[0009] Patent CN120600758A discloses a gradient composite cathode structure, an all-solid-state lithium-ion battery, and its fabrication method. It employs both micron- and nanon-scale sulfide solid electrolytes to construct a bilayer gradient structure along the electrode thickness direction. While this approach improves the balance between electron and ion transport, the nanon- and micron-scale solid electrolytes are located in different functional layers, failing to construct a clearly defined interface layer and ion transport framework at the scale of a single cathode particle. Its improvement is primarily felt along the electrode thickness direction, with limited improvement on the interface stability of the cathode particle surface and interface contact issues under low stacking pressure conditions.

[0010] In summary, while existing technologies can improve the ion transport performance of composite cathodes to some extent through particle size distribution optimization, surface coating, or gradient structure design, they still have the following common shortcomings: First, most of the interfaces formed are still physical contact interfaces, which are prone to contact degradation under low stacking pressure conditions, leading to a continuous increase in interface impedance; second, surface coating technologies are difficult to simultaneously construct a continuous long-range ion transport network between the particle interface and the bulk phase; third, existing technologies generally lack a systematic design for stabilizing the cathode particle-scale interface structure, making it difficult to simultaneously consider interface ion transport capacity, long-range ion transport capacity, and interface mechanical stability during cycling.

[0011] Therefore, how to construct a composite cathode structure that can achieve interface pre-construction, interface chemical reconstruction and interface mechanical stabilization under low stacking pressure conditions, while taking into account both interface ion transport capability and long-range ion transport capability, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0012] In view of the above-mentioned problems, the present invention provides a low-stacking-pressure sulfide all-solid-state battery composite cathode material, its preparation method, and its application. This composite cathode material exhibits low interfacial impedance and excellent cycle stability under low stacking pressure conditions.

[0013] To address the aforementioned problems, this invention provides a sulfide-based all-solid-state battery composite cathode material, comprising a high-nickel layered oxide cathode active material, a nanoscale sulfide solid electrolyte, a micron-scale sulfide solid electrolyte, an interface activator, and an amorphous adaptive ion buffer material.

[0014] In this invention, The nanoscale sulfide solid electrolyte adheres to the surface of the positive electrode active material particles, forming an interface pre-construction layer. The interface activator induces the interface structure reconstruction between the positive electrode active material and the nano-scale sulfide solid electrolyte through heat treatment, forming an interface transition layer. The micron-sized sulfide solid electrolyte is distributed in the gaps between adjacent positive electrode active material particles, forming a continuous long-range ion transport framework and spatially connected to the interface pre-constructed layer. The amorphous adaptive ion buffer material is filled between micron-sized sulfide solid electrolyte particles and in the contact area between the solid electrolyte and the positive electrode active material particles to form an amorphous ion buffer layer. The interface transition layer, interface preconstruction layer, amorphous ion buffer layer, and continuous long-range ion transport framework are distributed in a gradient along the direction from the surface of the cathode particles to the interparticle gaps, forming a multi-scale cooperative ion transport network.

[0015] Preferably, the chemical formula of the high-nickel layered oxide cathode active material is LiNi. x Co y Mn z O2, where 0.9≤x≤1.0, 0≤y≤0.1, 0≤z≤0.1, y and z are not simultaneously 0, and x+y+z=1; the chemical formula of the nanoscale sulfide solid electrolyte and the micron-scale sulfide solid electrolyte is Li. 6-a PS 5-a M 1+a , where M is Cl, Br or I, and 0≤a≤0.6.

[0016] Preferably, the particle size of the nanoscale sulfide solid electrolyte is 50~1000nm, and the particle size of the micron-scale sulfide solid electrolyte is 1~20μm.

[0017] For example, the particle size of the nanoscale sulfide solid electrolyte is 50~100nm, 100~500nm or 500~1000nm; the particle size of the micron-scale sulfide solid electrolyte is 1~20μm or 10~20μm.

[0018] Preferably, the interface activator is one or more of LiNbO3, Li3PO4, Li2ZrO3 and LiAlO2, and its addition amount accounts for 0.1~3wt% of the total mass of the composite cathode material.

[0019] Preferably, the amorphous adaptive ion buffer material is one or more of the following: Li3BO3-based glassy electrolyte, Li2O-B2O3-P2O5 system glassy electrolyte, Li2O-SiO2-P2O5 system glassy electrolyte, and Li3PO4-based glassy electrolyte, and its addition amount accounts for 0.5~10wt% of the total mass of the composite cathode material.

[0020] Preferably, it further includes a conductive agent, which is one or more of Super P, acetylene black, conductive graphite, conductive carbon black, carbon nanotubes, graphene, Ketjen black, and vapor-grown carbon fibers; based on the total mass of the composite cathode material, the mass percentages of the high-nickel layered oxide cathode active material, sulfide solid electrolyte, interface activator, amorphous adaptive ion buffer material, and conductive agent are 70~85wt%, 10~25wt%, 0.1~3wt%, 0.5~10wt%, and 1~5wt%, respectively.

[0021] Based on the same inventive concept, the present invention also provides a method for preparing a sulfide all-solid-state battery composite cathode material as described in any of the above claims, comprising the following steps: S1. Mix high-nickel layered oxide positive electrode active material, nano-scale sulfide solid electrolyte and interface activator to obtain premixed composite powder; S2. Add an organic grinding aid to the premixed composite powder and perform low-energy mechanical ball milling to allow the nano-sized sulfide solid electrolyte and interface activator to adhere to the surface of the high-nickel layered oxide positive electrode active material particles, forming interface pre-constructed composite particles. S3. The pre-constructed composite particles are vacuum dried to remove the organic grinding aid, thereby obtaining composite particles with a nanoscale interface coating structure. S4. The composite particles are subjected to heat treatment, and under the action of an interface activator, the interface structure between the high-nickel layered oxide positive electrode active material and the nano-scale sulfide solid electrolyte is reconstructed to form an interface transition layer. S5. Add micron-sized sulfide solid electrolyte, amorphous adaptive ion buffer material and optional conductive agent to the composite particles after interface reconstruction, and mix evenly to obtain the composite cathode material.

[0022] The preparation mechanism of this invention is as follows: This invention utilizes nanoscale Li 5.5 PS 4.5 Cl 1.5 Sulfide solid electrolyte, high-nickel ternary cathode material LiNi 0.9 Co 0.05 Mn 0.05 The interfacial self-assembly and selective adsorption behavior of O2 particles and the interfacial activator LiNbO3 during low-energy mechanical ball milling and chemical heat treatment enable nano-sized Li... 5.5 PS 4.5 Cl 1.5 It preferentially accumulates and adheres to the surface of high-nickel ternary cathode particles, while the interface activator LiNbO3 is uniformly dispersed in the contact area between the cathode particles and the nanoscale solid electrolyte, forming a reactive interface pre-constructed layer. Specifically: During the low-energy ball milling process, on the one hand, nano-sized Li 5.5 PS 4.5 Cl 1.5 Due to its high specific surface area and high surface activity, the LiNbO3 can break down the weak bonding regions on the surface of cathode particles under mechanical shearing, and preferentially adsorb onto the surface of high-nickel ternary cathode particles through interparticle friction, electrostatic interaction, and surface energy-driven action. On the other hand, the interface activator LiNbO3 can participate in the construction of the interface region, improving the contact uniformity between the cathode active material and the sulfide solid electrolyte, and providing reaction sites for subsequent thermally induced interface reactions. It is particularly important to note that the low-energy ball milling speed (50~500 rpm) used in this invention is crucial for maintaining the integrity of the sulfide solid electrolyte crystal structure. When the ball milling speed is too high (e.g., 1000 rpm), the mechanical shear energy exceeds the lattice tolerance threshold of the sulfide solid electrolyte, leading to the destruction of its crystal structure, the gradual disappearance of characteristic diffraction peaks, and a significant decrease in ionic conductivity, thus losing its interface pre-construction function. After low-energy ball milling, nano-sized LiNbO3... 5.5 PS 4.5 Cl 1.5 A uniform interfacial pre-construction layer is formed on the surface of the cathode particles with LiNbO3. However, at this stage, the contact between the nano-sized sulfide solid electrolyte and the cathode particles is still mainly physical adsorption, and the interfacial bonding strength is limited. After vacuum drying to remove the organic grinding aid, a nano-sized LiNbO3 layer is formed around the high-nickel ternary cathode particles. 5.5 PS 4.5 Cl 1.5 A composite interface pre-constructed layer composed of "-LiNbO3" was then formed. Subsequently, heat treatment at an appropriate temperature (200~400℃) allowed the interface activator LiNbO3 to exert a reaction-inducing effect in the cathode / sulfide solid electrolyte interface region, promoting the reaction of nano-sized Li 5.5 PS 4.5 Cl 1.5 With LiNi 0.9 Co 0.05 Mn 0.05Interfacial structure reconstruction occurs between O2 particles, forming an interfacial transition layer with higher chemical stability. This process differs from traditional heat treatment processes that only improve contact through particle sintering. Instead, it utilizes LiNbO3 to regulate the interfacial reaction pathway, transforming the cathode / solid electrolyte interface from a simple physical contact into a composite interfacial structure with stable chemical bonds. This reduces interfacial side reactions and ion transport obstacles caused by the space charge layer. Heat treatment temperature is a key control parameter: if the temperature is too low, the interfacial activation effect of LiNbO3 is insufficient, resulting in inadequate interfacial reconstruction and limited thickness and continuity of the interfacial transition layer; if the temperature is too high, the rate of side reactions in the interfacial region accelerates, potentially generating high-resistivity secondary phase products, which in turn disrupts the continuity of interfacial ion transport. Under conditions of 200–400℃ (300℃ being optimal), LiNbO3 can fully exert its interfacial activation-inducing effect, enabling nanoscale Li... 5.5 PS 4.5 Cl 1.5 A continuous, dense, and chemically stable interfacial transition layer is formed between the nanoscale interfacial layer and the NCM particle surface, enhancing the structural coupling between the nanoscale interfacial layer and the subsequently added micron-scale LPSC framework. Micron-scale Li is then added to the composite particles after interfacial reconstruction. 5.5 PS 4.5 Cl 1.5 And amorphous adaptive ion buffer materials, such as Li3BO3-based glassy electrolytes. Among them, micron-sized Li... 5.5 PS 4.5 Cl 1.5 Mainly distributed in the interstitial region between adjacent high-nickel ternary cathode particles, and associated with nano-sized Li on the particle surface. 5.5 PS 4.5 Cl 1.5Spatially connected at the interface layer, a continuous long-range ion transport framework is formed. Meanwhile, the amorphous adaptive ion buffer material Li3BO3 fills the spaces between micron-sized solid electrolyte particles and the contact area between the solid electrolyte and cathode particles, forming an amorphous ion buffer layer with a certain deformation adaptability. This amorphous adaptive ion buffer layer utilizes the characteristic of amorphous structures lacking long-range ordered lattice constraints. During battery cycling, it can release interfacial stress through local structural adjustments and fill microscopic contact defects caused by cathode material volume changes, particle rearrangement, and low stacking pressure conditions, thereby maintaining the continuous contact state of the solid-solid interface within the composite cathode. Unlike nano- or micron-sized sulfide solid electrolytes that rely on rigid lattices to maintain ion transport paths, the amorphous Li3BO3-based buffer layer, due to its structural flexibility and interfacial deformation adaptability, can follow the interface morphology changes during cathode particle volume expansion / contraction, preventing contact detachment between rigid particles due to mismatch. Simultaneously, the Li3BO3-based glassy electrolyte itself has a certain lithium-ion transport capacity; after filling the gaps between particles, it does not form an additional ion transport blocking layer but maintains ion transport continuity in the buffer region. Therefore, this invention ultimately constructs a multi-scale synergistic composite structure consisting of "high-nickel ternary cathode particle core, interface activation-induced reconstruction layer, nanoscale sulfide solid electrolyte interface layer, amorphous adaptive ion buffer layer, and micron-scale sulfide solid electrolyte ion transport framework layer".

[0023] From a spatial distribution perspective, this structure exhibits a clear gradient characteristic: close to LiNi 0.9 Co 0.05 Mn 0.05 The surface region of O2 particles is mainly composed of nano-sized Li. 5.5 PS 4.5 Cl 1.5 Composed of interface reconstruction products, it is used to stabilize the cathode / solid electrolyte interface; the interparticle region is mainly composed of micron-sized Li 5.5 PS 4.5 Cl 1.5 The structure provides a continuous ion transport path; the two are flexibly connected by an amorphous adaptive ion buffer material, achieving structural coordination between the interface region and the bulk region. Compared to the random distribution of cathode particles, solid electrolyte particles, and conductive agents in traditional mechanically mixed composite cathodes, where the components rely solely on external pressure to maintain contact, this invention achieves a structural transformation of the solid electrolyte components from random distribution to gradient and functionally partitioned distribution through interface pre-construction, interface-induced reconstruction, and amorphous buffer regulation. Among these components, nano-sized Li... 5.5 PS 4.5 Cl 1.5Primarily responsible for interfacial ion transport and interfacial stabilization at the cathode particle scale; the interfacial activator LiNbO3 induces the formation of a stable interfacial transition layer, reducing the chemical reaction resistance between the cathode and the sulfide solid electrolyte; the amorphous adaptive ion buffer layer handles stress release and solid-solid contact maintenance during cycling; micron-sized Li 5.5 PS 4.5 Cl 1.5 A long-range ion transport network is then constructed. The aforementioned multifunctional units, through spatial synergistic coupling, jointly enable the composite cathode to maintain stable interfacial contact and continuous ion transport capability under low stacking pressure conditions. This is also the core microstructural feature that distinguishes this invention from traditional mechanically mixed composite cathodes, single nano-solid electrolyte coating structures, and ordinary heat-treated modified systems.

[0024] Preferably, the organic grinding aid is one or more of anisole, toluene, xylene, cyclohexane, n-hexane, isobutyl isobutyrate, and butyl acetate; the ball milling speed is 50~500 rpm.

[0025] Preferably, in step S3, the drying temperature is 30~60℃; in step S4, the heat treatment temperature is 200~400℃, and the heat treatment is carried out under an inert gas atmosphere or vacuum conditions.

[0026] Based on the same inventive concept, the present invention also provides a sulfide all-solid-state battery, comprising the sulfide all-solid-state battery composite cathode material described in any one of the above claims or the sulfide all-solid-state battery composite cathode material prepared by any one of the above claims.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention employs a low-energy mechanical + chemical thermal treatment process to pre-construct nano-scale sulfide solid electrolyte, high-nickel layered oxide positive electrode active material, and interface activator. This allows the nano-scale sulfide solid electrolyte to preferentially adsorb and adhere to the surface of the positive electrode active material particles, while simultaneously achieving uniform distribution of the interface activator in the contact area between the positive electrode and the solid electrolyte, forming a reactive nano-scale interface pre-constructed layer. Compared with the traditional method of directly mechanically mixing the positive electrode active material, solid electrolyte, and conductive agent, this invention can transform the random distribution of solid electrolyte components into preferential enrichment on the surface of the positive electrode particles, increasing the effective contact area between the positive electrode active material and the solid electrolyte, reducing interfacial voids and local ion transport breakage areas, shortening the path of lithium ions migrating from the solid electrolyte to the interior of the positive electrode particles, thereby reducing interfacial ion migration resistance and improving the utilization rate of the positive electrode active material. (2) By introducing an interface activator, the present invention transforms the subsequent heat treatment process from a traditional particle sintering or contact strengthening process into an induced reconstruction process with interfacial chemical regulation. During the heat treatment process, the interface activator can promote the interfacial structure reorganization between the nano-scale sulfide solid electrolyte and the surface of the high-nickel cathode active material particles, forming a stable interfacial transition layer. This reconstructed interfacial structure can reduce the tendency of side reactions between the high-nickel cathode and the sulfide solid electrolyte, reduce the formation of high-resistivity interfacial products, and improve the continuity of lithium-ion cross-interfacial migration, thereby improving the stability of the composite cathode interface. (3) After completing the pre-construction of the nanoscale sulfide solid electrolyte interface and the thermally induced interface reconstruction, this invention further introduces micron-scale sulfide solid electrolyte to construct a long-range ion transport framework. Because micron-scale sulfide solid electrolyte has a large particle size and good space-filling ability, it can be mainly distributed in the gap region between adjacent positive electrode active material particles and form a spatial connection with the nanoscale solid electrolyte interface layer on the particle surface, thereby constructing a continuous sulfide solid electrolyte network. Compared with composite positive electrode structures that use only nanoscale solid electrolytes, this invention can avoid the problems of nanoparticle aggregation due to high specific surface area and discontinuous ion transport paths, thus improving the ion transport efficiency inside the composite positive electrode. (4) This invention further introduces an amorphous adaptive ion buffer material to construct an amorphous flexible ion buffer layer inside the composite cathode. The amorphous adaptive ion buffer material has a certain lithium-ion transport capacity and structural adjustment capability, and can fill the microscopic contact defects between sulfide solid electrolyte particles and between the cathode active material and the solid electrolyte. During battery cycling, when the cathode material undergoes volume changes or the external stacking pressure decreases, the amorphous buffer layer can alleviate interface stress concentration through local structural adjustment, reduce interparticle contact failure, and thus improve the stability of the solid-solid interface under low stacking pressure conditions; (5) This invention forms a multi-scale gradient structure with functional partitioning characteristics inside the composite cathode through the synergistic construction of a nanoscale sulfide solid electrolyte interface layer, an interface activation-induced reconstruction layer, an amorphous adaptive ion buffer layer, and a micron-scale sulfide solid electrolyte ion transport framework. Specifically, the nanoscale sulfide solid electrolyte mainly undertakes the interface ion transport function at the cathode particle scale; the interface activation reconstruction layer mainly undertakes the interface chemical stabilization function; the amorphous adaptive ion buffer layer mainly undertakes the contact maintenance and stress buffering function under low pressure conditions; and the micron-scale sulfide solid electrolyte mainly undertakes the long-range ion transport function inside the composite cathode. These multifunctional structural units form a continuous, stable, and mechanically adaptable ion transport network through spatial coupling. (6) The composite structure constructed in this invention can effectively reduce the dependence of sulfide all-solid-state batteries on high stacking pressure to maintain interfacial contact. In traditional random mixed composite cathodes, the components mainly rely on external pressure to maintain interparticle contact. When the stacking pressure is reduced, interfacial detachment and ion transport blockage are likely to occur. This invention, through interface preconstruction and amorphous adaptive buffering mechanism, enables a more stable intrinsic connection between the solid electrolyte and cathode particles. Even under low stacking pressure conditions, it can still maintain a high proportion of effective ion transport interface, thereby improving battery capacity utilization and cycle stability. (7) The preparation method adopted in this invention has both process simplicity and scalability. The interface is pre-constructed by low-energy ball milling, the interface is induced to reconstruct by heat treatment, and combined with the subsequent construction of solid electrolyte framework and amorphous buffer layer, a composite cathode material with multi-scale synergistic structure can be obtained without complex equipment or special processing conditions. Attached Figure Description

[0028] Figure 1 This is a SEM image of the composite cathode material of Comparative Example 6 of the present invention; Figure 2 Here is a SEM image of the composite cathode material of Example 1 of the present invention; Figure 3 The images show the XRD patterns of the composite cathode materials of Example 1 (milling speed of 300 rpm) and Comparative Example 7 (milling speed of 1000 rpm). Detailed Implementation

[0029] To make the present invention easier to understand, specific embodiments are described below to further illustrate the invention. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical terms used below have the same meaning as understood by those skilled in the art; unless otherwise specified, the raw materials and reagents involved herein can be purchased commercially or prepared by known methods.

[0030] It should be noted that the low stacking pressure range of this application is 0.1~50MPa.

[0031] To address the problems mentioned in the background section, this invention provides a low-stacking-pressure sulfide all-solid-state battery composite cathode material, its preparation method, and its applications. This composite cathode material exhibits low interfacial impedance and excellent cycle stability under low stacking pressure conditions.

[0032] The following examples and comparative models further illustrate this point.

[0033] It should be noted that the high-nickel layered oxide cathode active material used in the embodiments of this application is the high-nickel ternary cathode material LiNi. 0.9 Co 0.05 Mn 0.05 O2 (NCM); the sulfide solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 (LPSC); the interface activator is LiNbO3; the amorphous adaptive ion buffer material is Li3BO3-based glassy electrolyte; the conductive agent is vapor-grown carbon fiber (VGCF). The average particle size of the nano-sized LPSC particles is 100–500 nm, the average particle size of the micro-sized LPSC particles is 1–10 μm, the average particle size of the LiNbO3 particles is 100–500 nm, and the average particle size of the Li3BO3 particles is 0.5–5 μm. Cyclohexane was used as a grinding aid to promote the uniform adhesion of nano-sized LPSC and LiNbO3 to the surface of NCM particles during low-energy ball milling. Ball milling conditions: 300 rpm, 4 hours; Drying conditions: Vacuum drying at 45℃ for 12 hours; Heat treatment conditions: Argon protective atmosphere, heating rate 5℃ / min -1 .

[0034] Example 1 A method for preparing a low-stacking-pressure sulfide all-solid-state battery composite cathode material includes the following steps: (1) Weigh 79wt% NCM, 19wt% nano-sized LPSC and 2wt% LiNbO3 and mix them to obtain a premixed composite powder (the amount of each component in step (1) is based on the mass of the premixed composite powder). (2) Add cyclohexane as a grinding aid to the premixed composite powder (the mass ratio of cyclohexane to the mixed powder is 3:1), and wet ball mill at 300 rpm for 4 h to obtain interface pre-constructed composite particles. (3) The preconstructed composite particles were vacuum dried at 45°C for 12 h to remove cyclohexane and obtain composite particles with nanoscale interface coating structure. (4) The obtained composite particles were placed in an argon protective atmosphere furnace and heated at 5°C for 5 min. -1 The heating rate was increased to 300℃ and held for 6 hours to induce structural reconstruction of the interface between LiNbO3 and NCM and nanoscale LPSC, forming a stable interface transition layer. (5) Subsequently, micron-sized LPSC, Li3BO3-based glassy electrolyte and VGCF conductive agent are added to make the final composite cathode combination satisfy: NCM:LPSC:LiNbO3:Li3BO3:VGCF=74:22:2:1:1. After mixing evenly, the composite cathode material of the present invention is obtained.

[0035] Example 2 The difference between this embodiment and Embodiment 1 is that in step (4), the temperature is 5℃·min -1 The temperature was increased to 200°C and held for 6 hours, then allowed to cool naturally to room temperature. Other steps and parameters were the same as in Example 1.

[0036] Example 3 The difference between this embodiment and Embodiment 1 is that in step (4), the temperature is 5℃·min -1 The temperature was increased to 350°C and held for 6 hours, then allowed to cool naturally to room temperature. Other steps and parameters were the same as in Example 1.

[0037] Example 4 The difference between this embodiment and Embodiment 1 is that in step (1), 84 wt% NCM, 14 wt% nano-sized LPSC, and 2 wt% LiNbO3 are weighed and mixed. Other steps and parameters are the same as in Embodiment 1.

[0038] Example 5 The difference between this embodiment and Embodiment 1 is that in step (1), 89 wt% NCM, 9 wt% nano-sized LPSC and 2 wt% LiNbO3 are weighed and mixed. Other steps and parameters are the same as in Embodiment 1.

[0039] Example 6 The difference between this embodiment and Embodiment 1 is that in step (1), 94 wt% NCM, 4 wt% nano-sized LPSC, and 2 wt% LiNbO3 are weighed and mixed. Other steps and parameters are the same as in Embodiment 1.

[0040] Example 7 The difference between this embodiment and Embodiment 1 is that in step (5), the amount of Li3BO3 amorphous adaptive ion buffer material added is 3wt%. Other steps and parameters are the same as in Embodiment 1.

[0041] Example 8 The difference between this embodiment and Embodiment 1 is that in step (5), the amount of Li3BO3 amorphous adaptive ion buffer material added is 5wt%. Other steps and parameters are the same as in Embodiment 1.

[0042] Example 9 The difference between this embodiment and Embodiment 1 is that in step (5), Li3BO3 is replaced with Li3PO4 glassy electrolyte. Other steps and parameters are the same as in Embodiment 1.

[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that (1)-(4) are omitted, and 74wt% NCM, 22wt% nano-sized LPSC, 2wt% LiNbO3, 1wt% Li3BO3 and 1wt% VGCF are directly weighed and mixed to prepare a composite cathode. Other steps and parameters are the same as in Example 1.

[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that, in step (1), the LiNbO3 interfacial activator is not added. Other steps and parameters are the same as in Example 1.

[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that in step (5), Li3BO3 amorphous adaptive ion buffer material is not added. Other steps and parameters are the same as in Example 1.

[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that in steps (1) and (5), all added solid electrolytes are nanoscale LPSCs, and no microscale LPSCs are added. Other steps and parameters are the same as in Example 1.

[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that in steps (1) and (5), all added solid electrolytes are micron-sized LPSCs, and no nano-sized LPSCs are added. Other steps and parameters are the same as in Example 1.

[0048] Comparative Example 6 The difference between this comparative example and Example 1 is that step (4) is omitted, i.e., heat treatment is not performed. Other steps and parameters are the same as in Example 1.

[0049] Comparative Example 7 The difference between this comparative example and Example 1 is that in step (1), the ball mill speed is adjusted to 1000 rpm. Other steps and parameters are the same as in Example 1.

[0050] Performance testing and results analysis: The composite positive electrode sheets prepared in Examples 1-9 and Comparative Examples 1-7 were combined with a sulfide solid electrolyte membrane and a negative electrode to form an all-solid-state battery. Electrochemical performance was tested under the same stacking pressure at a temperature of 25°C. The specific steps for assembling the all-solid-state battery include: (1) Preparation of positive and negative composite electrodes: The samples obtained in the above examples and comparative examples were mixed with 1% polytetrafluoroethylene (PTFE) and fiberized, and then rolled on a roller press (rolling speed 5 m·min). -1 The composite positive electrode sheet is obtained by (with the temperature of both the upper and lower rollers being 80℃).

[0051] (2) Assembly of all-solid-state lithium-ion battery: Li-In alloy sheet, LPSC solid electrolyte membrane, and composite positive electrode sheet prepared in the above examples and comparative examples are stacked in a PEEK mold. Positive and negative electrode posts are inserted at both ends of the PEEK mold respectively. Densification is carried out under a pressure of 400MPa. Finally, the stacking pressure is fixed at 20MPa in a metal frame to obtain an all-solid-state battery.

[0052] The electrochemical performance of the above-mentioned all-solid-state lithium-ion battery was tested, and the results are shown in Table 1 below. The charge / discharge window is 2.1~3.7V (V vs. Li-In / Li). + Each battery needs to be activated three times before cycling, with an activation current of 0.1C (1C = 190 mA·g). -1 The circulating current is 0.5C (1C = 190mA·g). -1 ).

[0053] Table 1:

[0054] Analysis of the data in Table 1 shows that: As can be seen from the comparison of Examples 1-3, a suitable heat treatment temperature can significantly improve the overall electrochemical performance of the composite cathode material. When the heat treatment temperature is increased from 200℃ to 300℃, the initial discharge specific capacity increases from 201.12 mAh·g. -1 Increased to 210.91 mAh·g -1 The initial coulombic efficiency increased from 84.47% to 85.95%, and the discharge specific capacity after 100 cycles increased from 137.12 mAh·g⁻¹. -1 Increased to 169.43 mAh·g -1 However, when the heat treatment temperature was further increased to 350℃, all properties decreased. This indicates that there is a suitable heat treatment window for the interface reconstruction induced by the LiNbO3 interface activator. At 300℃, LiNbO3 can promote the formation of a continuous and stable interfacial transition layer between NCM and nanoscale LPSC, and enhance the structural coupling between the nanoscale interfacial layer and the micron-scale LPSC framework, making interfacial ion transport more continuous. At lower temperatures, the degree of interface reconstruction is insufficient; while when the temperature is further increased to 350℃, interfacial side reactions begin to increase, affecting interfacial continuity, and therefore the overall performance decreases.

[0055] A comparison of Examples 1 and 4-6 shows that as the proportion of nanoscale LPSCs gradually decreases during the pre-construction stage, the initial discharge specific capacity of the composite cathode material increases from 210.91 mAh·g. -1 Gradually decreased to 199.24 mAh·g -1 The discharge specific capacity after 100 cycles also increased from 169.43 mAh·g -1 Decreased to 124.28 mAh·g -1 This indicates that the degree of pre-construction of the nano-sized LPSC interface directly affects the interfacial transport capability of the composite cathode. This is because nano-sized LPSC preferentially adheres to the surface of NCM particles during wet ball milling to form a continuous interfacial layer, which serves as the basis for subsequent interfacial reconstruction. When the content of nano-sized LPSC is appropriate, it can fully cover the surface of the cathode particles and form a continuous connection with the subsequently added micron-sized LPSC framework. As the proportion of nano-sized LPSC decreases, the interfacial coverage gradually becomes insufficient, and the spatial coupling between the interfacial layer and the framework layer weakens, resulting in increased interfacial impedance and decreased ion transport continuity.

[0056] As can be seen from the comparison between Examples 1 and Examples 7-8, after introducing the Li3BO3-based amorphous adaptive ion buffer layer, the composite cathode materials all exhibit excellent cycle stability, with the capacity retention rate maintained above 91% after 100 cycles, while the initial discharge specific capacity remains at 203-211 mAh·g. -1 Within the range of (rounded to the nearest integer). With further increases in the amount of Li3BO3 added, the initial discharge specific capacity decreased slightly, while the discharge specific capacity remained essentially stable after cycling, indicating that an appropriate amount of amorphous buffer layer was added. This is because the Li3BO3-based amorphous buffer layer can fill the microscopic gaps between the cathode particles and the solid electrolyte, and relies on the strong stress regulation capability of the amorphous structure to continuously maintain effective solid-solid interface contact during cycling, reducing the probability of interface delamination and localized failure. When its addition amount further increases, it occupies a portion of the volume fraction of the highly ionicly conductive phase and active material, thus slightly reducing the initial capacity.

[0057] As can be seen from the comparison between Example 1 and Comparative Examples 1 and 6, the initial discharge specific capacity of Example 1 reaches 210.91 mAh·g. -1 Comparative Examples 1 and 6 were only 62.86 mAh·g, respectively. -1 and 190.57mAh·g -1 The discharge specific capacity after 100 cycles in Examples 1, 1 (Comparative Example), and 6 (Comparative Example 6) was 169.43 mAh·g. -1 22.29mAh·g -1 and 121.45mAh·g -1This demonstrates a significant synergistic effect between interface preconstruction and interface activation-induced reconstruction. Comparative Example 1, using only traditional mechanical mixing, resulted in random contact between components, making it difficult to establish a continuous and stable ion transport interface. While Comparative Example 6 formed a nanoscale LPSC interface layer, the lack of heat treatment prevented LiNbO3 from activating the interface, and the contact between the interface layer, NCM particles, and the micron-scale LPSC framework remained primarily physical. Example 1, however, sequentially completed interface preconstruction and interface activation-induced reconstruction, further densifying the interface layer and forming a continuous and stable hierarchical structure, thus exhibiting the best overall performance.

[0058] A comparison of Example 1 and Comparative Examples 2-3 shows that removing the LiNbO3 interface activator or the Li3BO3 amorphous adaptive ion buffer layer both lead to a decrease in the overall performance of the composite cathode. Specifically, the initial discharge specific capacity of Comparative Examples 2 and 3 decreased to 196.41 mAh·g. -1 and 198.73mAh·g -1 After 100 cycles, the discharge specific capacity decreased to 122.19 mAh·g. -1 and 124.77mAh·g -1 The results were significantly lower than in Example 1. This indicates that LiNbO3 and Li3BO3 perform different interface regulation functions. LiNbO3 mainly acts during the heat treatment stage, inducing structural reconstruction at the NCM / LPSC interface to improve interfacial bonding strength and ion transport efficiency; Li3BO3 mainly acts during the cycling stage, alleviating interfacial stress and maintaining solid-solid contact stability through its amorphous structure. Both components act in the interface formation and service stages respectively, jointly improving the long-term stability of the composite cathode. Therefore, the absence of either component makes it difficult to obtain optimal overall performance.

[0059] As can be seen from the comparison between Example 1 and Comparative Examples 4, 5, 7, and 8, the overall electrochemical performance of the composite cathode material decreased to varying degrees after replacing the technical solution of this invention with single-scale LPSC, high-energy ball milling, or other glassy buffer materials. Specifically, the specific capacity after 100 discharge cycles in Comparative Examples 4 and 5 decreased to 121.02 mAh·g. -1 and 116.71mAh·g -1 The first discharge specific capacity of Comparative Example 7, prepared by high-energy ball milling, was only 88.06 mAh·g. -1 Furthermore, the cycling performance also deteriorates significantly. This is because nanoscale LPSCs are prone to aggregation, making it difficult to form a continuous bulk ion transport framework; while micron-scale LPSCs lack sufficient interface coverage. Figure 3As shown, at a ball milling speed of 300 rpm, the LPSC solid electrolyte can maintain its complete crystal structure, while at a ball milling speed of 1000 rpm, the characteristic peaks of the LPSC solid electrolyte gradually disappear. This indicates that high-energy ball milling will destroy the LPSC crystal structure, reduce its ionic conductivity, and increase interface defects. This invention, through the synergistic design of nanoscale LPSC interface preconstruction, LiNbO3 interface activation-induced reconstruction, Li3BO3-based amorphous adaptive ion buffer layer, and micron-scale LPSC framework network, achieves simultaneous optimization of rapid interfacial transport, continuous bulk transport, and long-term interfacial stability, thereby significantly improving the overall electrochemical performance of the composite cathode under low stacking pressure conditions.

[0060] The products prepared in Example 1 and Comparative Example 6 were analyzed by scanning electron microscopy, and the results are as follows: Figure 1-2 As shown, by Figure 1 It can be seen that the material particles in Comparative Example 6, which only underwent the low-energy ball milling step, were more dispersed, indicating that the low-energy ball milling step could only achieve a uniform mixing effect; therefore, Figure 2 It is known that further heat treatment can promote the interfacial reconstruction of the nanoscale LPSC interface layer, enabling it to form a tighter and more continuous hierarchical coupling structure with the NCM particle surface and the micron-scale LPSC framework, thereby completing the construction of the gradient composite microstructure.

[0061] A comparison of Examples 1 and 9 shows that replacing the Li3BO3 amorphous adaptive ion buffer material with a Li3PO4 glassy electrolyte leads to a decrease in the overall performance of the composite cathode. The initial discharge specific capacity of Example 9 decreased to 197.29 mAh·g. -1 The initial coulombic efficiency decreased to 83.45%, and the discharge specific capacity decreased to 124.60 mAh·g after 100 cycles. -1 The results were significantly lower than in Example 1. This indicates that although different types of glassy electrolytes can improve the interfacial contact within the composite cathode, their structural characteristics and interfacial control capabilities differ significantly. Li3BO3 exhibits high structural disorder and good interfacial adaptability. During cycling, it can alleviate local stress caused by NCM particle volume changes through its flexible amorphous network, maintaining continuous contact between the cathode active material and the solid electrolyte, while simultaneously promoting rapid Li+ migration at the solid-solid interface. In contrast, Li3PO4, due to the high stability of its PO4 tetrahedral network structure and strong interfacial rigidity, has relatively insufficient adaptability to interfacial deformation and stress release under low stacking pressure cycling conditions, leading to obstructed ion transport in some interfacial regions. Therefore, although both Li3BO3 and Li3PO4 can act as glassy ion conductors for interfacial control, Li3BO3 achieves a better balance between ion transport capability, interfacial continuity, and mechanical buffering capacity, making it more suitable for low-stack-pressure sulfide all-solid-state battery systems.

[0062] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A sulfide-based all-solid-state battery composite cathode material, characterized in that, This includes high-nickel layered oxide cathode active materials, nanoscale sulfide solid electrolytes, micron-scale sulfide solid electrolytes, interface activators, and amorphous adaptive ion buffer materials; among them, The nanoscale sulfide solid electrolyte adheres to the surface of the positive electrode active material particles to form an interface pre-construction layer. The micron-sized sulfide solid electrolyte is distributed in the gaps between adjacent positive electrode active material particles to form a continuous long-range ion transport framework. The amorphous adaptive ion buffer material is filled between particles to form an amorphous ion buffer layer; The interface activator is heat-treated to induce interface reconstruction and form an interface transition layer.

2. The sulfide all-solid-state battery composite cathode material according to claim 1, characterized in that, The chemical formula of the high-nickel layered oxide positive electrode active material is LiNi. x Co y Mn z O2, where 0.9≤x≤1.0, 0≤y≤0.1, 0≤z≤0.1, y and z are not simultaneously 0, and x+y+z=1; the chemical formula of the nanoscale sulfide solid electrolyte and the micron-scale sulfide solid electrolyte is Li. 6-a PS 5-a M 1+a , where M is Cl, Br or I, and 0≤a≤0.

6.

3. The sulfide all-solid-state battery composite cathode material according to claim 1, characterized in that, The nanoscale sulfide solid electrolyte has a particle size of 50~1000nm, and the microscale sulfide solid electrolyte has a particle size of 1~20μm.

4. The sulfide all-solid-state battery composite cathode material according to claim 1, characterized in that, The interface activator is one or more of LiNbO3, Li3PO4, Li2ZrO3 and LiAlO2, and its addition amount accounts for 0.1~3wt% of the total mass of the composite cathode material.

5. The sulfide all-solid-state battery composite cathode material according to claim 1, characterized in that, The amorphous adaptive ion buffer material is one or more of the following: Li3BO3-based glassy electrolyte, Li2O-B2O3-P2O5 system glassy electrolyte, Li2O-SiO2-P2O5 system glassy electrolyte, and Li3PO4-based glassy electrolyte, and its addition amount accounts for 0.5~10wt% of the total mass of the composite cathode material.

6. The sulfide all-solid-state battery composite cathode material according to claim 1, characterized in that, It also includes a conductive agent, which is one or more of Super P, acetylene black, conductive graphite, conductive carbon black, carbon nanotubes, graphene, Ketjen black and vapor-grown carbon fibers; based on the total mass of the composite cathode material, the mass percentages of high-nickel layered oxide cathode active material, sulfide solid electrolyte, interface activator, amorphous adaptive ion buffer material and conductive agent are 70~85wt%, 10~25wt%, 0.1~3wt%, 0.5~10wt% and 1~5wt%, respectively.

7. A method for preparing a sulfide all-solid-state battery composite cathode material as described in any one of claims 1, characterized in that, Includes the following steps: S1. Mix high-nickel layered oxide positive electrode active material, nano-scale sulfide solid electrolyte and interface activator to obtain premixed composite powder; S2. Add an organic grinding aid to the premixed composite powder and perform low-energy mechanical ball milling to allow the nano-sized sulfide solid electrolyte and interface activator to adhere to the surface of the high-nickel layered oxide positive electrode active material particles, forming interface pre-constructed composite particles. S3. The pre-constructed composite particles are vacuum dried to remove the organic grinding aid, thereby obtaining composite particles with a nanoscale interface coating structure. S4. The composite particles are subjected to heat treatment, and under the action of an interface activator, the interface structure between the high-nickel layered oxide positive electrode active material and the nano-scale sulfide solid electrolyte is reconstructed to form an interface transition layer. S5. Add micron-sized sulfide solid electrolyte, amorphous adaptive ion buffer material and optional conductive agent to the composite particles after interface reconstruction, and mix evenly to obtain the composite cathode material.

8. The preparation method according to claim 7, characterized in that, In step S2, the organic grinding aid is one or more of anisole, toluene, xylene, cyclohexane, n-hexane, isobutyl isobutyrate, and butyl acetate; the ball milling speed is 50~500 rpm.

9. The preparation method according to claim 7, characterized in that, In step S3, the drying temperature is 30~60℃; in step S4, the heat treatment temperature is 200~400℃, and the heat treatment is carried out under an inert gas atmosphere or vacuum conditions.

10. A sulfide all-solid-state battery, characterized in that, The sulfide all-solid-state battery composite cathode material comprising any one of claims 1-6 or the sulfide all-solid-state battery composite cathode material prepared by the preparation method according to any one of claims 7-9.

Citation Information

Patent Citations

  • Method for reducing grain boundary impedance and interface impedance of oxide electrolyte

    CN111509293A

  • Positive electrode conductive filler, solid-state battery positive electrode, solid-state battery and preparation method of solid-state battery

    CN116706064A

  • Multilayer composite solid electrolyte membrane and preparation method and application thereof, and all-solid-state battery

    CN117059879B

  • Gradient composite positive electrode structure, all-solid-state lithium ion battery and preparation method

    CN120600758A

  • All-solid-state battery, positive electrode and positive electrode material thereof and preparation method

    CN121922591A